Nuclear Receptor Cofactors in PPARγ-Mediated Adipogenesis and Adipocyte Energy Metabolism. (19th December 2006) - Powell, Emily; Kuhn, Peter; Xu, Wei
Abstract : Transcriptional cofactors are integral to the proper function and regulation of nuclear receptors. Members of the peroxisome proliferator-activated receptor (PPAR) family of nuclear receptors are involved in the regulation of lipid and carbohydrate metabolism. They modulate gene transcription in response to a wide variety of ligands, a process that is mediated by transcriptional coactivators and corepressors. The mechanisms by which these cofactors mediate transcriptional regulation of nuclear receptor function are still being elucidated. The rapidly increasing array of cofactors has brought into focus the need for a clear understanding of how these cofactors interact in ligand- and cell-specific manners. This review highlights the differential effects of the assorted cofactors regulating the transcriptional action of PPARγ and summarizes the recent advances in understanding the physiological functions of corepressors and coactivators.